2009
DOI: 10.1007/s10661-009-0920-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal concentration in the Khoshk River water and sediment, Shiraz, Southwest Iran

Abstract: Heavy metal contents and contamination characteristics of the water and sediment of the Khoshk River, Shiraz, Southwest Iran were investigated. The abundance of heavy metals decreases as Zn > Mn > Cr > Ni >Pb > Cu > Cd in water samples and Mn > Cr > Pb > Ni > Zn > Cu > Cd in sediments, respectively. Based on the enrichment factor and geoaccumulation index values, sediments were loaded with Cr, Zn, Pb, Cu, and Cd. Pearson correlation matrix as well as cluster and principal components analyses and analysis of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(64 citation statements)
references
References 33 publications
2
59
1
2
Order By: Relevance
“…The nonsignificant differences between levels of Cd and Pb in some stations indicate that these metals originate from the same source of pollution. The concentrations of heavy metals in this study were higher than those reported by Salati and Moore (2010) in the Khoshk River at Shiraz, Iran and those found in Sava River in Serbia (Vukovic et al, 2011).…”
Section: Discussioncontrasting
confidence: 82%
“…The nonsignificant differences between levels of Cd and Pb in some stations indicate that these metals originate from the same source of pollution. The concentrations of heavy metals in this study were higher than those reported by Salati and Moore (2010) in the Khoshk River at Shiraz, Iran and those found in Sava River in Serbia (Vukovic et al, 2011).…”
Section: Discussioncontrasting
confidence: 82%
“…Enrichment factor (EF) differentiates the influence of anthropogenic contributions from natural factors on metal variations in the sediment [2]. In the present study, Al is the main component of clay mineral [45] and has been used to normalize geochemical data due to its conservative behavior [47][48].…”
Section: Enrichment Factor (Ef)mentioning
confidence: 99%
“…
Heavy metals pollution is a worldwide problem that has grown during the past few decades because of their toxicity, extensive sources, non-biodegradable characteristics, and accumulative behaviors in aquatic environments [1][2][3]. These metals are identified as a significant indicator for degradation of aquatic environments.
…”
mentioning
confidence: 99%
“…These quality index method has proved to be a significant tool for effectively gathering a composite influence of indicators to the overall contamination [11]. Several evaluation methods have been utilized by various authors in heavy metal pollution assessment in soils and sediments: Single index factor (Pi), Nemerow's pollution index (PN), potential ecological risk index (RI), enrichment factor (EF), contamination factor (CF), geoaccumulation index (Igeo), contamination index (Cd), pollution load index (PLI) as well as hazard quotient [12][13][14][15][16][17][18][19][20]. Pi and CF are computed as basis for obtaining PN and PLI respectively.…”
Section: Introductionmentioning
confidence: 99%